2004
DOI: 10.4049/jimmunol.173.4.2245
|View full text |Cite
|
Sign up to set email alerts
|

TNF Family Member B Cell-Activating Factor (BAFF) Receptor-Dependent and -Independent Roles for BAFF in B Cell Physiology

Abstract: The cytokine TNF family member B cell-activating factor (BAFF; also termed BLyS) is essential for B cell generation and maintenance. Three receptors have been identified that bind to BAFF: transmembrane activator, calcium modulator, and cyclophilin ligand interactor (TACI); B cell maturation Ag (BCMA); and BAFF-R. Recently, it was shown that A/WySnJ mice, which contain a dramatically reduced peripheral B cell compartment due to decreased B cell life span, express a mutant BAFF-R. This finding, together with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
370
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(405 citation statements)
references
References 56 publications
30
370
3
2
Order By: Relevance
“…To simplify the data representation we refer to these as "E47" RT-PCR. Sizes of the detected PCR products were 452 (GAPDH) (Frasca et al, 2004a); 454 bp (E2A) (Frasca et al, 2004a); 606 bp (AID) (Frasca et al, 2004a;Jabara et al, 2002); 429 bp (γ 1 GLTs) (Muramatsu et al, 2000); 353 bp (γ 1 PSTs) (Muramatsu et al, 2000); 600 bp (BAFF-R) (Sasaki et al, 2004); 405 bp (TACI) (primers designed in our lab); 415 bp (BCMA) (primers designed in our lab).…”
Section: Rna Extraction Reverse Transcription and Pcr (Rt-pcr)mentioning
confidence: 84%
“…To simplify the data representation we refer to these as "E47" RT-PCR. Sizes of the detected PCR products were 452 (GAPDH) (Frasca et al, 2004a); 454 bp (E2A) (Frasca et al, 2004a); 606 bp (AID) (Frasca et al, 2004a;Jabara et al, 2002); 429 bp (γ 1 GLTs) (Muramatsu et al, 2000); 353 bp (γ 1 PSTs) (Muramatsu et al, 2000); 600 bp (BAFF-R) (Sasaki et al, 2004); 405 bp (TACI) (primers designed in our lab); 415 bp (BCMA) (primers designed in our lab).…”
Section: Rna Extraction Reverse Transcription and Pcr (Rt-pcr)mentioning
confidence: 84%
“…The TNF family member BAFF and one of its receptors BAFF-R play a crucial role in the developmental progression of transitional B cells into the mature B-cell compartments. This is best exemplified by the fact that BAFF-and BAFF-R-deficient mice have a very severe block at the T1 stage of B-cell development [72][73][74][75][76]. Moreover, we recently showed that BAFF-BAFF-R signaling is also required for the survival of follicular and marginal zone B cells [77].…”
Section: Transitional Splenic B Cellsmentioning
confidence: 99%
“…A separate study by Enzler et al showed that all major components of the non-classical NF-κB pathway are crucial for BAFF-mediated survival [26•]. Further, while knockout mice for the components of each pathway differ slightly, all are essentially similar to BAFF −/− or BAFFr −/− mice [20,[34][35][36]. Thus, it seems likely that the BCR and BAFFr are coupled through these two signaling systems, either via simultaneous activation targeting separate promoters of survival, or through direct cross-talk.…”
Section: Baff/baffr Signaling Integrates Primary B Cell Selection Andmentioning
confidence: 99%